EFFECTIVENESS OF VIRTUAL REALITY (VR) TO ENHANCE THE TRAINING AND EDUCATION OF DENTAL STUDENTS, FOCUSING ON SKILL ACQUISITION AND RETENTION - Dr Madiha Anwar; Dr Tanzeela Shaikh; Dr Ayesha Tahir; Dr Rehab Falaq; Dr Oumama Khalil; Dr Ahsan Shafiq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective This study aims to evaluate the effectiveness of Virtual Reality (VR) in enhancing the training and education of dental students, focusing on skill acquisition and retention. Methodology A systematic review was performed to examine the application of VR in dental education. A systematic search of databases PubMed, Scopus Web of Science, and Google Scholar was conducted to identify studies published in English between January 2010 and September 2024 that addressed this gap. The types of studies included randomized controlled trials, cohort studies and observational studies. Data on study characteristics (authors, year of publication), VR technologies, training duration, skill acquisition outcomes and retention outcomes were collected. We conducted meta-analysis to pool results, and used narrative synthesis method to summarize the findings. Results VR-based training, with its capacity to immerse students in realistic situations, significantly enhances the clinical skills adquisition and conservation of dental students compared to traditional methods. VR offered benefits for variation in scenario simulations; real-time feedback and practice repetition were some of the most frequently mentioned. Nonetheless, the challenges related to high upfront capital costs, technological infrastructure requirements and no common protocols were also noted. Conclusion VR shows substantial potential to revolutionize dental education by providing an immersive, flexible, and effective learning environment. Despite the challenges, the benefits of VR warrant its inclusion in dental training paradigms. Future research should focus on standardizing VR training protocols and evaluating its long-term impact on clinical competencies and patient outcomes.